Indole alkaloid glycosides with a 1'-(phenyl)ethyl unit from Isatis indigotica leaves - Qinglan Guo; Dawei Li; Chengbo Xu; Chenggen Zhu; Ying Guo; Haibo Yu; Xiaoliang Wang; Jiangong Shi (Elsevier, 2020)
Seven indole alkaloid glycosides containing a 1'-(4"-hydroxy-3",5"-dimethoxyphenyl)ethyl unit (1-7) were isolated from an aqueous extract of Isatis indigotica leaves (da qing ye). Their structures were determined by spectroscopic data analysis combined with enzymatic hydrolysis as well as comparison of their experimental CD (circular dichroism) and calculated ECD (electrostatic circular dichroism) spectra. Based on analysis of [α]D20 and/or Cotton effect (CE) data of 1-7, two simple roles to assign location and/or configuration of β-glycopyranosyloxy and 1'-(phenyl)ethyl units in the indole alkaloid glycosides are proposed. Stereoselectivity in plausible biosynthetic pathways of 1-7 is discussed. Compounds 3 and 4 and their mixture in a 3:2 ratio showed activity against KCNQ2 in CHO cells. The mixture of 5 and 6 (3:2) exhibited antiviral activity against influenza virus H1N1 PR8 with IC50 64.7 μmol/L (ribavirin, IC50 54.3 μmol/L), however, the individual 5 or 6 was inactive. Preliminary structure-activity relationships were observed.